Catalpol Protects Against Spinal Cord Injury in Mice Through Regulating MicroRNA-142-Mediated HMGB1/TLR4/NF-κB Signaling Pathway - Xia, Hougang; Wang, Dandan; Guo, Xiaohui; Wu, Kaidi; Huang, Fuwei; Feng, Yanjiang (Frontiers in Pharmacology, 2021)
Background: Spinal cord injury (SCI) is a devastating condition that leads to paralysis, disability and even death in severe cases. Inflammation, apoptosis and oxidative stress in neurons are key pathogenic processes in SCI. Catalpol (CTP), an iridoid glycoside extracted from Rehmannia glutinosa, has many pharmacological activities, such as anti-inflammatory, anti-oxidative and anti-apoptotic properties. Purpose: Here, we investigated whether CTP could exert neuroprotective effects against SCI, and explored the underlying mechanism involved. Methods: SCI was induced by a weight-drop device and treated with CTP (10mg and 60 mg/kg). Then the locomotor function of SCI mice was evaluated by the BBB scores, spinal cord edema was measured by the wet/dry weight method, oxidative stress markers and inflammatory factors were detected by commercial kits and neuronal death was measured by TUNEL staining. Moreover, the microRNA expression profile in spinal cords from mice following SCI was analyzed using miRNA microarray. In addition, reactive oxygen species (ROS) generation, inflammatory response and cell apoptosis were detected in murine microglia BV2 cells under oxygen-glucose deprivation (OGD) and CTP treatment. Results: Our data showed that CTP treatment could improve the functional recovery, as well as suppress the apoptosis, alleviate inflammatory and oxidative response in SCI mice. In addition, CTP was found to be up-regulated miR-142 and the protective effects of CTP on apoptosis, inflammatory and oxidative response may relate to its regulation of HMGB1/TLR4/NF-κB pathway through miR-142. Conclusion: Our findings suggest that CTP may protect the spinal cord from SCI by suppression of apoptosis, oxidative stress and inflammatory response via miR-142/HMGB1/TLR4/NF-κB pathway.